Strategical Approach for the Neutronics in the European Fusion Programme. (17th November 2021) - Leichtle, D.; Fischer, U.; Bachmann, C.
Abstract: One of the main aims of the European fusion programme is the design of a DEMOnstration fusion power plant (DEMO). The related work is conducted by the EUROfusion consortium and includes a strong supporting research and development programme. Support is also provided to the design of the high intense neutron source IFMIF-DONES (International Fusion Material Irradiation Facility-DEMO Oriented NEutron Source) to be built for the qualification of materials considered for DEMO. Neutronics plays a fundamental role for the design, operation, and safety of these facilities including the evaluation and verification of their nuclear performance. The lessons learned during the ITER design and construction phase point to the need to strengthen nuclear design integration already in the early DEMO design phase and establish an improved nuclear safety culture. This requires a coordinated approach for the neutronics that relies upon the availability of suitable computational procedures, tools, and data, qualified and validated for specific design- and safety-related applications. Accordingly, the approach builds on the development of advanced computation tools and the provision of high-quality nuclear data supported by integral experiments for their validation. Furthermore, configuration and requirement management principles ensure the alignment with the global nuclear design integration. This translates into appropriately chosen design margins and acceptance criteria, along with the specification of the nuclear analyses to be conducted in the various design phases. This paper presents the outlined approach as implemented in the EUROfusion Power Plant Physics and Technology (PPPT) programme and provides a strategical outlook of planned activities. This includes development works on advanced simulation tools with their application in various nuclear design- and safety-related analyses. The efforts to improve the nuclear database, in particular, with regard to radiation damage and activation cross-section data relevant to DEMO and DONES, are highlighted. Furthermore, the methodological approach applied to PPPT nuclear analyses including design, shielding, activation, and radiation dose calculations is discussed on the basis of specific examples.